Ảnh hưởng của chất lượng dịch vụ hỗ trợ bởi trí tuệ nhân tạo đến ý định mua hàng lặp lại của khách hàng trên sàn thương mại điện tử tại Việt Nam - Lê Văn, Chiến; Nguyễn Hồng, Quân; Dương Thị Hoài, Nhung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
In the highly competitive landscape of e-commerce, customer service has become a key factor in creating a competitive advantage. The integration of artificial intelligence (AI) into customer service is emerging as a breakthrough trend. This study aims to examine the impact of AI-powered service quality on customers’ repurchase intentions on B2C e-commerce platforms in Vietnam, mediated by perceived value and customer satisfaction, and moderated by the fit between AI functionality and customer capability. Survey data were collected from 512 consumers who had experienced AI services on platforms such as Shopee, Tiki, Lazada, and TikTok Shop. The findings shed light on the role of AI in optimizing user experience and boosting repurchase intentions, while also offering recommendations for enhancing service quality and strengthening customer loyalty.